Protein purification using zeolite adsorbent - Farhani, Faisal (2009)
There has been much interest generated in the development of protein purification since many of modern biotechnology products can be produce from purified protein such as insulin, vaccines and food additives. The aim of this research is to study the most optimum condition to purify protein in order to produce a high purity protein with low cost by applying the principle adsorption process using zeolite adsorbent. Adsorption of Bovine Serum Albumin used as protein sample on Y, Beta and ZSM-5 zeolites at various pH values was carried out in sequence to investigate the effect of different pH value and different types of adsorbent on protein purification. Batch adsorption experiment was carried out by contacting the same amount of different zeolites synthesized with the Bovine Serum Albumin solution. Outcome of the experiment shows that maximum adsorption capacity occurred when Y zeolite was used as the adsorbent at pH 5 that is close to isoelectric point (pI) of Bovine Serum Albumin which is 4.7. This proves that adsorption capacity depends on the physicochemical properties of the zeolite as well as the pH of protein solution. The maximum adsorption on the zeolites tended to occur when the pH was at or just below the pI of the protein. At this pH, the protein sample is positively charged. Adsorption isotherms obtained on effect of different type of adsorbent at pH5 and effect of different pH on Y zeolite were found to be confirmed well to the ideal Langmuir model equation. In order to improve in the next study, other parameters such as protein size, temperature of the protein solution and protein concentration need to be considered as well.